Legalization of Medical Marijuana Use in Cerebral Palsy Cases (Analysis of Constitutional Court Decision No. 106/PUU-XVIII/2020) - M Fadli Habibie (International Journal Reglement & Society (IJRS), 2022)
This research began with an application submitted to the constitutional court by the mother of a victim of cerebral palsy to collect various information related to treatment carried out in the same case using marijuana abroad, with the hope that Indonesia can legalize marijuana in the medical world in particular. This type of research is a normative juridical research using secondary data by processing data from primary legal materials, secondary legal materials and tertiary law. Based on the results of the research, it is known that several conventions prohibit the use of drugs in non-medical matters, but in medical matters they can still be excluded as well as related to their use in the development of science. When associated with several cases of cerebral palsy in various countries in the world such as the US Foods and Drugs Administration (FDA) or the United States drug and food control agency approved the drug Epidiolex (cannabidiol / (CBD)). This drug is the first FDA-approved drug that contains a pure base of marijuana. Narcotics Category I as formulated in the Elucidation norm of Article 6 paragraph (1) letter a and Article 8 paragraph (1) of the Narcotics Law makes the use of all types of Narcotics Category I for treatment/health services impossible in Indonesia. Then the National Narcotics Agency (BNN), this cannabis plant contains a compound THC (tetrahydrocannabinol), a narcotic substance that causes euphoria (a feeling of pleasure continuously for no reason) in users, so it contains substances that are not good. for public health. The element of THC causes intoxication (poisoning) in the wearer, heart palpitations with an increase of 50%, plus redness of the eyeball due to dilation of capillary blood vessels. From the research above, it can be concluded that the Constitutional Court Decision No. 106/PUU-XVIII/2020 the implications of the prohibition of Narcotics Category I as formulated in the Elucidation norm of Article 6 paragraph (1) letter a and Article 8 paragraph (1) of the Narcotics Law make the use of all types of Narcotics Category I for treatment/health services unable to be used. carried out in Indonesia. The government itself explains that drugs for the treatment of Epilepsy and Cerebral Palsy do not contain Narcotics